Association between Self-Reported Bruxism and Sleeping Patterns among Dental Students in Saudi Arabia: A Cross-Sectional Study - Shereen M. Shokry; Eman E. El Wakeel; Nassr Al-Maflehi; Zaheera RasRas; Nida Fataftah; Enam Abdul Kareem (International Journal of Dentistry)
Objectives. The aim of this cross-sectional study was to identify sleeping patterns among dental students and their association with self-reported bruxism in Riyadh Colleges of Dentistry and Pharmacy (RCsDP). Methods. A cross-sectional study was performed including 549 students (67 men and 482 women). A structured questionnaire was adopted from The PSQI (The Pittsburgh Sleep Questionnaire Index) used for data collection. It included questions which are categorized into sleeping habits, sleep-related symptoms, and additional questions concerning bruxism. This questionnaire was randomly distributed among all college preclinical and postclinical students. Sleep bruxism diagnosis was based on self-reported data. The data were analyzed using Chi-square tests through SPSS software for Windows. Results. Statistical analyses revealed significant correlations between self-reported bruxism and sleeping habits including sleep initiation (χ2=22.6, p=0.000), continuous sleep until morning (χ2=19.2, p=0.001), nighttime sleep duration (χ2=20.2, p=0.000), and length of daytime naps (χ2=28.35, p=0.000). There was an association between self-reported bruxism and sleeping-related symptoms including awakening early in the morning before the usual time without a cause (χ2=16.52, p=0.000) and increased nightmares (χ2=13.7, p=0.001). Conclusions. Poor sleeping pattern was an important factor among dental students, who reported sleep bruxism.